The prevalence and sociodemographic determinants of uninvestigated dyspepsia in the Czech Republic: a multicentre prospective study accomplished 10 years after the first study from the same geographical areas. Issue 1 (January 2018) - Rejchrt, Stanislav; Koupil, Ilona; Kopáčová, Marcela; Škodová Fendrichová, Miluška; Seifert, Bohumil; Voříšek, Viktor; Špirková, Jana; Douda, Tomáš; Tachecí, Ilja; Bureš, Jan
Abstract : Objective: The epidemiology of uninvestigated dyspepsia was studied in the Czech Republic for the first time in 2001. The aim of the current multicenter prospective study was to evaluate dyspepsia using the same methods in a representative sample of general unselected population from the same geographical areas 10 years later. Participants and methods: A total of 38 147 individuals comprised the general population for a random two-step selection process. A total of 1836 participants (863 males and 973 females; aged 5–98 years) took part in the questionnaire-based study. Helicobacter pylori status was investigated in all participants by means of 13 C-urea breath test. Results: The overall prevalence of dyspepsia was 2.6% among children and adolescents aged 5–17 years and 16.0% among adults aged 18–98 years. We did not detect any statistically significant sex differences in the prevalence of total dyspepsia or its subtypes. Overall, 2.4% of H. pylori -negative children and adolescents aged less than 18 years reported dyspepsia, and 16.8% of H. pylori -negative adults reported it. Among H. pylori -positive children and adolescents and adults, dyspepsia was present in 8.3 and 15.8%, respectively. Type A dyspepsia (as the only long-lasting symptom) was statistically significantly associated with H. pylori status among children and adolescents. Among adults aged 18 years or older, we noted a lower prevalence of dyspepsia in adults with elementary education compared with university education. Current use of antibiotics was associated with an increased prevalence of dyspepsia in adults. Conclusion: Despite the substantial decrease of H. pylori infection in the Czech Republic over the past 10 years, the prevalence and sociodemographic determinants of uninvestigated dyspepsia did not change significantly.